Minimizing atelectasis formation during general anaesthesia—oxygen washout is a non-essential supplement to PEEP. (3rd April 2017) - Östberg, Erland; Auner, Udo; Enlund, Mats; Zetterström, Henrik; Edmark, Lennart
Abstract: Background: Following preoxygenation and induction of anaesthesia, most patients develop atelectasis. We hypothesized that an immediate restoration to a low oxygen level in the alveoli would prevent atelectasis formation and improve oxygenation during the ensuing anaesthesia. Methods: We randomly assigned 24 patients to either a control group ( n  = 12) or an intervention group ( n  = 12) receiving an oxygen washout procedure directly after intubation. Both groups were, depending on body mass index, ventilated with a positive end-expiratory pressure (PEEP) of 6–8 cmH2 O during surgery. The atelectasis area was studied by computed tomography before emergence. Oxygenation levels were evaluated by measuring blood gases and calculating estimated venous admixture (EVA). Results: The atelectasis areas expressed as percentages of the total lung area were 2.0 (1.5–2.7) (median [interquartile range]) and 1.8 (1.4–3.3) in the intervention and control groups, respectively. The difference was non-significant, and also oxygenation was similar between the two groups. Compared to oxygenation before the start of anaesthesia, oxygenation at the end of surgery was improved in the intervention group, mean (SD) EVA from 7.6% (6.6%) to 3.9% (2.9%) ( P  = .019) and preserved in the control group, mean (SD) EVA from 5.0% (5.3%) to 5.6% (7.1%) ( P  = .59). Conclusion: Although the oxygen washout restored a low pulmonary oxygen level within minutes, it did not further reduce atelectasis size. Both study groups had small atelectasis and good oxygenation. These results suggest that a moderate PEEP alone is sufficient to minimize atelectasis and maintain oxygenation in healthy patients.